UPAYA INDONESIA DALAM PENGUATAN USAHA MIKRO KECIL MENENGAH UNTUK MENGAHADAPI ASEAN ECONOMIC COMMUNITY 2015 (STUDI KASUS: INDUSTRI KECIL MENENGAH KERAJINAN KAYU BALI TAHUN 2010-2014) - Indria Rizky Arafah; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research aims to provide more knowledge to students and public about the effort in conducting the Indonesian Government to strengthen the micro, small, and medium enterprises to confront the ASEAN Economic Community by 2015, particularly on small and medium industry of Bali’s wood crafts in Bali.The research method that used in this study is a qualitative method, which begins with collecting, arranging and enterprising data. This research is an explanatory that describes a problem, symptoms, policies, and actions. Based on the phenomenon that is used as the problems to be studied by the author. While the author uses theory of role and foreign policy, and globalization theory to answer the basic problems that the authors including in this writing. Level analysis that the author used in this research is nation-state.The 2020 acceleration of ASEAN Economic Community to be coming 2015 is one of the seriousness from the fellow countries of ASEAN to realize the economic cooperation in Southeast Asia. Indonesia will be confronted with the opportunity and defiance at once when the ASEAN free trade enforced. To abuse the opportunity, Indonesia makes efforts in Micro, Small, and Medium Enterprises reinforcement with increase competitiveness Micro, Small, and Medium Enterprises in Indonesia. Micro, Small, and Medium Enterprises is one of important sector in Indonesia that have to empowered, because it gave significant contribution in Indonesia’s economic matters. Indonesia has prepare many various of program and wisdom to increase the Indonesia’s Micro, Small, and Medium Enterprises and Small Medium Industry competitiveness to confront the ASEAN Economic Community by 2015.Key Word: ASEAN Economic Community 2015, Micro, Small, and Medium Enterprises, Small Medium Industry.